Influence of localized thermal effects on the reconstitution kinetics of lactose-coated whole milk powder. (December 2021) - Angelopoulou, Diamanto; Meunier, Vincent; Forny, Laurent; Niederreiter, Gerhard; Palzer, Stefan; Salman, Agba D.
Graphical abstract: Highlights: At 40 °C/400 rpm, amorphous micronized lactose improves reconstitution, crystalline has the opposite effect. Dissolution enthalpy of the coating material could influence the surface fat properties. No differences at 800 rpm or if whole milk powder is agglomerated. Abstract: Reconstitution of dairy powders is strongly influenced by the presence and physical state of fat on the particle surface. The present study investigates the effect of a micronized lactose coating on the physical state of the fat and the reconstitution kinetics of whole milk powder at four different temperatures (4/21/40/60 °C) and two stirring rates (400/800 rpm). For this purpose, two types of micronized lactose were used as coating materials: crystalline and amorphous. At 4 °C and 21 °C, the coated powders sink and are reconstituted faster than pure whole milk powder, regardless of the stirring rate applied. At 40/60 °C and 400 rpm, although the amorphous micronized lactose coating leads to a significant decrease in the reconstitution time, the crystalline coating has the opposite effect (or no effect). This discrepancy is related to the large differences in terms of dissolution enthalpy between the two micronized lactose physical states. It is posited that the dissolution of the coating material causes a temperature shift at the powder-water interface which could hamper the complete melting of surface fat and influence its viscosity, thereby affecting wetting and sinking. These differences are overcome at a high stirring rate (800 rpm) or if agglomerated whole milk powder is used as the host material.